The role of irradiation in the management of the axilla in early breast cancer patients - Elumalai, Thiraviyam; Jain, Urvashi; Coles, Charlotte E.; Benson, John R. (Frontiers in Oncology, 2023)
The need for axillary radiotherapy in patients with invasive breast cancer (IBC) has been a topic of great debate in the last decade. Management of the axilla has evolved significantly over the past four decades with a trend towards de-escalation of surgical interventions and the aim of reducing morbidity and enhancing QOL without compromising long-term oncology outcomes. This review article will address the role of axillary irradiation with a focus on the omission of completion axillary lymph node dissection in selected patients with sentinel lymph node (SLN) positive early breast cancer (EBC) with reference to current guidelines based on evidence to date.